Analysis of the Relationship between Mathematical Reasoning and Problem Solving of Elementary Students Mathematics Material: Analisis Hubungan Penalaran Matematis dengan Pemecahan Masalah terhadap Materi Matematika Siswa SD - Mardiah Nursoffina; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2022)
Mastery of mathematical reasoning and problem solving skills is very necessary for students, in order to understand and solve mathematical material better. The formulation of the problem in this research are (1) What are the advantages and disadvantages of mathematical reasoning ability?, (2) What are the advantages and disadvantages of problem solving ability?, (3) What is the relationship between mathematical reasoning ability and problem solving in mathematical material?. This type of research is a literature study. Sources of data used are secondary data sources. Data collection techniques were carried out by analyzing several articles in journals, related to the research focus taken by the researcher. The data analysis technique used is to analyze secondary data sources. In the learning process these two abilities must exist and cannot be separated, so it can be stated that they have a very close relationship. Mastery of mathematical reasoning and problem solving skills is very necessary for students, in order to understand and complete mathematical material better. The formulation of the problem in this research are (1) What are the advantages and disadvantages of mathematical reasoning ability?, (2) What are the advantages and disadvantages of problem solving ability?, (3) What is the relationship between mathematical reasoning ability and problem solving in mathematical material?. This type of research is a literature study. Sources of data used are secondary data sources. Data collection techniques were carried out by analyzing several articles in journals, related to the research focus taken by the researcher. The data analysis technique used is to analyze secondary data sources. In the learning process these two abilities must exist and cannot be separated, so it can be stated that they have a very close relationship.